PENGEMBANGAN MEDIA PEMBELAJARAN Si BaRu (APLIKASI BANGUN RUANG) BERBASIS AUGMENTED REALITY PADA MATA PELAJARAN MATEMATIKA MATERI BANGUN RUANG KELAS IV SEKOLAH DASAR - Indy Nila Rosada; Aries Tika Damayani; Mudzanatun (STKIP Subang, 2023)
This research aims to develop Si BaRu (Space Build Application) learning media based on Augmented Reality with space building material for grade IV elementary school students. This type of research is a type of research and development (Research and Development) using the ADDIE development model. Media in this research and development must go through assessment subjects in the form of validation of media experts, material experts, teacher response questionnaires, and student response questionnaires in order to strengthen media validation. The results of the development are in the form of Augmented Reality-based application media. Augmented Reality-based application learning media is declared valid as evidenced by the results of validation by learning media experts by 98%, material expert validation by 95%. Si BaRu (Building Space Application) learning media based on Augmented Reality is also declared practical with the results of teacher responses by 100% and from student responses by 88.8%. This can be concluded if the Si BaRu (Building Space Application) learning media based on Augmented Reality in mathematics subjects, building materials for grade IV elementary schools is valid and suitable for use in grade IV elementary schools.